Menuju Penegakan Hukum yang Lebih Berkeadilan dan Responsif - Ulum, Muh. Bachrul (Fakultas Syariah IAIN Purwokerto, 2010)
Law enforcement in Indonesia which still based on the legal positivism model is suitable for the type of Indonesia law. The model emphasized legal rules based on legal justice, but it failed to make substantial justice. Therefore law enforcement in Indonesia must be switched to a new model of law enforcement to actualize substantial and responsive justice because the principal function of law attends to man not otherwise.